2011
DOI: 10.1111/j.1472-765x.2010.02994.x
|View full text |Cite
|
Sign up to set email alerts
|

FISH analysis of Lactobacillus biofilms in the gastrointestinal tract of different hosts

Abstract: Aims: To investigate the spatial organization of endogenous and exogenously applied Lactobacillus communities at specific locations in the adult gastrointestinal tract of different hosts. Methods and Results: Samples of the human, murine and avian gastrointestinal tract of subjects that received or not received a Lactobacillus probiotic were analysed by fluorescence in situ hybridization (FISH) with rRNA-targeted probes. High levels of endogenous lactobacilli were observed on the nonsecretory, stratified squam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Prior to FISH analysis, serial paraffin sections of 7 m thickness were placed on positively charged slides (SuperFrost Plus, Braunschweig, Germany). FISH was performed as described by Lebeer et al (2011). Enzymatic mixture and hybridization buffer were used according to Czerwiń ski et al (2012).…”
Section: Fluorescence In Situ Hybridization (Fish) Analysismentioning
confidence: 99%
“…Prior to FISH analysis, serial paraffin sections of 7 m thickness were placed on positively charged slides (SuperFrost Plus, Braunschweig, Germany). FISH was performed as described by Lebeer et al (2011). Enzymatic mixture and hybridization buffer were used according to Czerwiń ski et al (2012).…”
Section: Fluorescence In Situ Hybridization (Fish) Analysismentioning
confidence: 99%
“…Endogenous Lactobacilli have been demonstrated to exist in biofilm-like communities in the avian and murine guts, while exogenously applied Lactobacillus spp. had difficulty establishing themselves [15]. This work suggests that factors that enhance biofilm formation and adhesion will be important both for the establishment of the native flora and for potential probiotics, to improve their ability to compete and if possible colonise.…”
Section: Introductionmentioning
confidence: 98%
“…The mucin proteins are heavily O-glycosylated and these glycans can serve as adhesion sites for commensal bacteria (118123). Several studies have shown that intestinal communities can be visualized as biofilms of sessile microorganisms within the mucus layer (116, 124126). High bacterial cell density within biofilms favors a mode of communication using diffusible small molecules as a mechanism for regulating biofilm formation and for social interactions (97, 127).…”
Section: Signaling Compoundsmentioning
confidence: 99%